Co-variation of hydrochemistry, inorganic nitrogen, and microbial community composition along groundwater flowpath: A case study in Linzhou-Anyang area, Southern North China plain. (May 2022) - Guo, Liang; Xie, Qian; Sheng, Yizhi; Wang, Guangcai; Jiang, Wanjun; Tong, Xiaoxia; Xu, Qingyu; Hao, Chunbo
Abstract: The exogenous input of nitrate in groundwater may change microbial community, and in turn, the change of microbial community affects the biogeochemical transformation of nitrate. However, how this mutual interaction varies along the groundwater flowpath remains poorly understood. Herein, we investigated the co-variation of hydrochemical characteristics and microbial community compositions in nitrate-contaminated groundwater along a generalized flowpath in Linzhou-Anyang area, southern North China Plain. The groundwater-rock interactions and human activities collectively controlled the transition patterns of hydrogeochemical conditions. Along the groundwater flowpath, the nitrate, ammonia, major ions, total organic carbon (TOC), C/N, and relative abundance of Proteobacteria and Epsilonbacteraeota subsequently increased, while nitrite, oxidation reduction potential (ORP), and overall microbial diversity decreased. Both microbial community composition and microbial co-occurrence network were primarily governed by the levels of TOC, nitrate, and nitrite, a sum of which explained 48.4% variance of community compositions, greater than the effect of water-rock interaction (basically ion contents, 12.9%) and ORP (4%), suggesting the dominant role of exogenous nitrate and organic carbon inputs in shaping microbial community. Accordingly, the variations of keystone bacterial lineages, e.g., Vogesella sp., Acinetobacter sp., Rhodoferax sp., Pseudomonas sp., and Flavobacterium sp., and archaeal lineage Candidatus Nitrosoarchaeum along the groundwater flowpath were putatively involved in the dissimilatory nitrate reduction, indicating the potential role of heterotrophic nitrate reducers in nitrate transformation. Our findings suggest that microbial community distribution along groundwater flowpath is intimately related to exogenous nitrate and organic carbon inputs, which likely outweigh the effect of groundwater circulation or water-rock interaction. This study could help us to better understand the inter-relationship between hydrochemical environments and microbial communities in nitrate-polluted groundwater. Highlights: Increased nitrate, ammonia, and TOC and decreased nitrite and ORP along flowpath. Proteobacteria and Epsilonbacteraeota increased along flowpath. Microbial communities in groundwater are shaped by nitrate, TOC, and nitrite. Nitrogen-related microbes accumulated in the groundwater downstream.